Toll-like receptor-4 antagonist (D)-naltrexone protects against carbamyl- platelet activating factor (cPAF)-induced preterm labor in mice - Wahid, Hanan Hamimi; Peck, Yin Chin; J.Sharkey, David; Diener, Kerrilyn R.; Hutchinson, Mark R.; Rice, Kenner C.; Moldenhauer, Lachlan M.; Robertson, Sarah A. (Elsevier Inc., 2020)
Spontaneous preterm labor is frequently caused by an inflammatory response in the gestational tissues elicited by either infectious or sterile agents. In sterile preterm labor, the key regulators of inflammation are not identified, but platelet-activating factor (PAF) is implicated as a potential rate-limiting effector agent. Since Toll-like receptor (TLR)-4 can amplify PAF signaling, we evaluated whether TLR4 contributes to inflammation and fetal loss in a mouse model of PAF-induced sterile preterm labor, and whether a small-molecule TLR4 inhibitor, (þ)-naltrexone, can mitigate adverse PAF-induced effects. The administration of carbamyl (c)-PAF caused preterm labor and fetal loss in wild-type mice but not in TLR4-deficient mice. Treatment with (þ)-naltrexone prevented preterm delivery and alleviated fetal demise in utero elicited after cPAF administered by i.p. or intrauterine routes. Pups born after cPAF and (þ)-naltrexone treatment exhibited comparable rates of postnatal survival and growth to carrier-treated controls. (þ)-Naltrexone suppressed the cPAF-induced expression of inflammatory cytokine genes Il1b, Il6, and Il10 in the decidua; Il6, Il12b, and Il10 in the myometrium; and Il1b and Il6 in the placenta. These data demonstrate that the TLR4 antagonist (þ)-naltrexone inhibits the inflammatory cascade induced by cPAF, preventing preterm birth and perinatal death. The inhibition of TLR4 signaling warrants further investigation as a candidate strategy for fetal protection and delay of preterm birth elicited by sterile stimuli.